Gravitational wave from dark sector with dark pion - Tsumura, Koji; Yamada, Masatoshi; Yamaguchi, Yuya (Journal of cosmology and astroparticle physics, 2017)
In this work, we investigate the spectra of gravitational waves produced by chiral symmetry breaking in dark quantum chromodynamics (dQCD) sector. The dark pion (π) can be a dark matter candidate as weakly interacting massive particle (WIMP) or strongly interacting massive particle (SIMP). For a WIMP scenario, we introduce the dQCD sector coupled to the standard model (SM) sector with classical scale invariance and investigate the annihilation process of the dark pion via the 2π → 2 SM process. For a SIMP scenario, we investigate the 3π → 2π annihilation process of the dark pion as a SIMP using chiral perturbation theory. We find that in the WIMP scenario the gravitational wave background spectra can be observed by future space gravitational wave antennas. On the other hand, when the dark pion is the SIMP dark matter with the constraints for the chiral perturbative limit and pion-pion scattering cross section, the chiral phase transition becomes crossover and then the gravitational waves are not produced.